Immediate and short-term effects of single-task and motor-cognitive dual-task on executive function - Weibin Zhang; Hua Liu; Tong Zhang (PLoS ONE, 2023)
Objectives Executive function plays an important role in our daily life and can be affected by both single task (acute aerobic exercise or cognitive training) and dual-task (acute motor-cognitive training) interventions. Here we explored the immediate and short-term effect on executive function to texted whether dual-task interventions are more effective at promoting executive function. Methods Forty-six young men were recruited (mean age: 20.65 years) and assigned randomly to aerobic exercise (n = 15), cognitive training (n = 15), or dual-task (n = 16) groups. Executive functions were assessed before, immediately after, and 30 min after intervention using Go/No-go, 2-back, and More-Odd-Shifting tests. Results Working memory function improved after all three interventions (significant Time effect, F(2,86) = 7.05, p = 0.001). Performance on the 2-back test was significantly better immediately after dual-task intervention (p = 0.038) and the response time was shorter (p = 0.023). Performance on the More-Odd-Shifting test improved over time (significant Time effect, F(2,86) = 30.698, p = 0.01), both immediately after the dual-task intervention (p = 0.015), and 30 min later (p = 0.001). Shifting-test performance was also better immediately after (p = 0.005) and 30 min after (p < 0.001) aerobic exercise. Conclusion Executive function was enhanced by single-task (acute aerobic exercise or cognitive training) and dual-task interventions. The effect continued for 30 min after both the single-task aerobic exercise and the dual-task intervention. For short-term intervention, the dual-task was not more effective than either of the single tasks.